2020
DOI: 10.1007/s10964-020-01304-z
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Multiple Forms of Bias Victimization on Youth and Young Adults: Relationships with Trauma Symptomatology and Social Support

Abstract: Research has documented that a significant portion of youth are exposed to bias victimization. However, less is known about whether experiencing certain types of bias victimization (e.g., sexual orientation bias) is more or less likely to be related to a more extensive bias victimization history (i.e., experiencing multiple types of bias victimization) and whether exposure to multiple types of bias victimization explains any relationships between specific types of bias victimization and negative outcomes. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…Rates were three times higher among LGB students compared to the other two student groups for experiencing bullying victimization plus homophobic verbal victimization. This finding coincides with previous studies conducted in Spain and other countries, which have reported a higher "amount" of victimization among sexual minority youth (Garaigordobil & Larrain, 2020;Mitchell et al, 2020). This leads us to believe that aspects of homophobic bullying may be characterized as amplified patterns of bullying, as also suggested in previous research (e.g., Espelage & Swearer, 2008;Espelage et al, 2018), in which bullying and homophobic aggressive behaviors are mainly targeted toward LGB students, but also toward other non-heteronormative students (LGBTQ +) not assessed in this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Rates were three times higher among LGB students compared to the other two student groups for experiencing bullying victimization plus homophobic verbal victimization. This finding coincides with previous studies conducted in Spain and other countries, which have reported a higher "amount" of victimization among sexual minority youth (Garaigordobil & Larrain, 2020;Mitchell et al, 2020). This leads us to believe that aspects of homophobic bullying may be characterized as amplified patterns of bullying, as also suggested in previous research (e.g., Espelage & Swearer, 2008;Espelage et al, 2018), in which bullying and homophobic aggressive behaviors are mainly targeted toward LGB students, but also toward other non-heteronormative students (LGBTQ +) not assessed in this study.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, poly-victimization-the experience of multiple kinds of victimization-has shown to have a significant effect on emotional impact; it is also related to trauma symptoms (Felix et al, 2009;Mitchell et al, 2020). However, the majority of poly-victimization studies either include other victimization types unrelated to bullying (e.g., Johns et al, 2021;Sterzing et al, 2019) or refer to general bullying (Espelage et al, 2016); they fail to cover homophobic and bullying victimization together.…”
Section: Emotional Impact and Consequences Of Homophobic Verbal And Bullying Victimizationmentioning
confidence: 99%
“…For instance, bullying victimization (i.e., physical, verbal, or relational peer aggression that is usually repeated and involves a power imbalance; Olweus, 1993), could lead to fear even if the incident is non-criminal. Similarly, hate speech-a heinous but often non-criminal act-could lead to fear and is disproportionately inflicted upon Black and Hispanic youth, as race and ethnicity are the most common statuses attacked by bias-based victimization (Mitchell et al, 2020). Furthermore, fear tends to be higher after biasrelated than non-biased victimization (McDevitt et al, 2001).…”
Section: Racial/ethnic Variation In the Fear-victimization Gapmentioning
confidence: 99%
“…Largely absent from this work is a thorough investigation of the degree to which bias-based revictimization occurs as well as the degree to which bias victimization overlaps with other forms of victimization (e.g., nonbias physical assaults or sexual violence). Not until recently has work shown that these patterns of victimization exist within the context of bias victimization and that they have significant deleterious effects on trauma-related symptomatology (Mitchell et al, 2020). Given their growing presence in the U.S., it is important to expand this work on bias victimization to Latinxs.…”
Section: Bias-motivated Polyvictimization and Revictimizationmentioning
confidence: 99%